Sistem Informasi Penjualan Pupuk di PT. HURIP UTAMA Berbasis Web - Rani Sri Wahyuni; Ilham Ferdiansyah; Asep Yusapra Salim; Yayan Heru Haerudin; Komara, Mutiara Andayani (Sekolah Tinggi Teknologi Wastukancana, 2024)
The development of the business world is marked by the increasing number of companies being established, both in the industrial, trade, and service sectors. In companies, information technology is crucial and must be optimally used for various purposes, one of which is in the sales field. PT. Hurip Utama is a company engaged in the fertilizer sales service, acting as a distributor for PT. Pupuk Kujang, located at Jln. Ahmad Yani No. 39 Dawuan Cikampek. PT. Hurip Utama faces issues in the sales system because the sales input process still relies on spreadsheets, and transactions are carried out manually, such as visiting the company for transactions. The design of an information system is a solution to address these issues by conducting transactions through a website. In developing this information system, a Flowmap model is used, and the system design employs Unified Modeling Language (UML). The software used to build the fertilizer sales information system is based on the CodeIgniter framework, using the PHP programming language version 7.4.9. The database is built on MySQL version 10.4.14, and testing is performed using Blackbox testing. The implementation of this sales management information system is expected to help increase fertilizer sales and also facilitate transactions for involved parties.